Psychological factors and recovery from trauma. (May 2020) - Schemitsch, Christine; Nauth, Aaron
Highlights: Symptoms of depression, anxiety and PTSD are common in orthopaedic trauma patients. Patients with higher levels of psychological dysfunction have shown increased levels of pain and dysfunction post-operatively. The implementation of effective screening programs and subsequent intervention programs are highly desirable. Abstract: Recent research has identified a high prevalence of psychological illnesses in patients who have sustained orthopaedic trauma. Depressive symptoms in this patient population have been reported to range from 13% to as high as 56%. Moreover, symptoms of depression, catastrophic thinking, and post-traumatic stress disorder (PTSD), have been consistently shown to negatively impact patient outcomes following treatment for their traumatic injuries. Specifically, patients with higher levels of psychosocial dysfunction have shown increased levels of pain, disability, and complications throughout their recovery. However, current research in orthopaedic trauma continues to be substantially focused on the physical and technical factors involved in the treatment of orthopaedic injuries. More research which applies the "biopsychosocial model" of health and evaluates the significant impact of psychological and social factors on recovery from trauma is needed. In particular, investigation which evaluates effective screening strategies and interventions to treat psychosocial dysfunction during recovery from trauma is highly desirable. This article reviews the current state of knowledge in this area and suggests future directions for research.